Mistaken modernity : India between worlds - "Gupta,Dipankar" (New Delhi, 2000)
From Hindu notions of dirt, South Asia's preference for women leaders to patronage in democratic politics, Dipankar Gupta resolves many of the paradoxes of contemporary India in this book. In the process, he issues a damning indictment of the"westoxicated" elitist Indian middle class, and shows how unmodern the people of this class are in the very areas in which they are considered to be modern. Modernity, argues the author, is not about technology and consumption, as is mistakenly believed in India, but has to do with attitudes, especially those that come into play in our social relations. It is here that the Indian middle class is found severely wanting. Family connections, privileges of caste and status, as well as the willingness to break every law in the book characterize our social relations very deeply. The past clings tenaciously to our present - traditional India thrives in contemporary locales. A brilliant and chilling treatise on the hypocrisy and vanity of the Indian middle class, and its pathetic attempts to cloak its traditional ways in superficial modernity.
Keywords: Sociology